HİDROJEN ATOMUYLA (H) LİTYUM HİDRÜR MOLEKÜLÜ (LİH) ARASINDAKİ ETKİLEŞMENİN İNCELENMESİ - DEMİR, SEVİM (Fırat Üniveristesi, 2014)
Hidrojen Atomuyla (H) Lityum Hidrür Molekülü (LİH) Arasındaki Etkileşmenin İncelenmesi Bu tezçalışmasında H+ LiHreaksiyonu hem değişimhemde depletion kanallarıiçinCentrifigul Sudden metoduylazamanabağlıdalgapaketikullanılarkaraştırılmıştır. Toplamreaksiyonihtimaliyetleri, tesirkesitlerivehızsabitleribulundu.Toplamreaksiyonihtimaliyetleritoplamaçısalmomentumun 0'dan 45'e kadarkideğerleriiçinhesaplandı. Anahtarkelimeler :Centrifigul Sudden yaklaşımı, tesirkesiti, hızsabiti

Investigation of the interaction between LiH molecule with hydrogen atom(H) In this thesis H+LiH,reaction has been investigated using a time dependent quantum mechanical wave packet method within the Centrifugal Sudden(CS) approximation for both the exchange and depletion channels. Total reaction probabilities, cross section and rate constants were found for initial rotation states. Total reaction probabilities were calculated for values from 0 to 45 of the total angular momentum. Keywords: Centrifugal Sudden approximation, cross section, rate constants,
Investigation of the interaction between LIH molecule with hydrogen atom (H)
Keywords: Fizik ve Fizik Mühendisliği